Geometrically Enabled Soft Electroactuators via Laser Cutting. Issue 11 (22nd August 2019) - Yan, Bingxi; Ma, Chunping; Zhao, Yinghao; Hu, Nan; Guo, Liang
Abstract : Recent advances in soft electroactuators (EAs) have inspired diverse novel artificial muscles and dexterous robots. Despite a rapidly expanding library of electroactive materials, precise and repeatable structuring remains a challenge. Existing EAs often involve post‐synthesis hand‐assembling of supportive components such as hingers, linkages, adhesives, and coatings to fulfill demanding functions. Following a different enabling strategy, herein, a straightforward laser‐patterning approach to directly embed functional 2D structures into electroactive polypyrrole (PPy) films is presented, thereby transforming their typical bending actuation into various demanding action modes including squeezing, gripping, flapping, and lifting in an electrolyte solution analog to body fluids in vivo. Such geometrically enabled movements prove controllable and modulable and are dictated primarily by the embedded patterns rather than materials or specific fabrication approach. The integrity of our soft EAs not only avoids laborious assembling and device fatigues but also further enables systematic structural design and geometrical fine‐tuning of deformations through fast mechanical simulation. This design strategy suggests broad opportunities in pattern‐augmented capabilities for next‐generation EAs and soft robotics. Abstract : Geometrically enabled functions of soft electroactuators are explored through systematic simulation‐guided laser patterning. Rational combinations of 2D geometries here demonstrate an appealing capability of transforming the bending actuation of polypyrrole films into demanding actions including lifting, gripping, flapping, and squeezing, while essentially providing high reproducibility and mechanical robustness. These discoveries highlight a geometrical strategy to unlocking numerous pattern‐augmented robotic functions.